A New Technique for Parallel Image Denoising. Issue 3 (July 2015) - Mustafa, Zeinab A.; Abrahim, Banazier A.; Tom, Khawther M.; Garma, Fatehia B.
Abstract : Parallel MATLAB is an extension of MATLAB that takes advantage of multicore desktop machines and clusters. In this article, we present a new method of description of the PID parallel image denoise techniques. PID has been designed with the goal of letting the parallel application programmer have the complete control about how his application is parallelized and at the same time freeing him from the burden of managing explicitly a large number of threads and associated synchronization and communication primitives. We do modify in some filters algorithm to denoise the image processing in parallel term; by this method, we speed up computations by using multiple processors and utilize more memory than available on a single machine. Experimental results are presented to demonstrate the parallel speedup obtained, and the output images produced by the parallel routines exactly matched the output images produced by the sequential routines.